Orthodontic Elastic Separator-Induced Periodontal Abscess: A Case Report - Talia Becker; Alex Neronov (Case Reports in Dentistry, 2012)
Aim. Orthodontic elastic bands were proposed as being the source of gingival abscesses that can rapidly lead to bone loss and teeth exfoliation. We report an adolescent, otherwise, healthy patient whose periodontal status was sound. Shortly after undergoing preparations for orthodontic treatment consisting of orthodontic separators, he presented with a periodontal abscess for which there was no apparent etiology. A non-orthoradial X-ray was inconclusive, but an appropriate one revealed a subgingival orthodontic separator as the cause of the abscess. Removal of the separator and thorough scaling led to complete resolution of the abscess, but there was already residual mild damage to the alveolar bone. Summary. Failure to use appropriate imaging to reveal the cause of gingival abscesses can result in the delay of implementing treatment and halting irreversible alveolar bone loss. An inflammatory process restricted to the gingiva and refractive to conventional therapy should raise the possibility of a foreign body etiology.